Pupuk Organik Cair Kulit Pisang untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Stroberi (Fragaria vesca L.) - Reza Puspita Sari; Irawati Chaniago; Zulfadly Syarif (Fakultas Pertanian, Universitas Warmadewa, 2020)
An experiment has been set in a completely randomized design to determine the best concentration of liquid organic fertilizer of peels of ‘kepok’ banana to increase the growth and yield of strawberry. The experiment was conducted at Nagari Koto Baru Simalanggang, Payakumbuh, the Regency of Lima Puluh Kota, West Sumatra from April to August 2019. The place lies at elevation about 540 m above sea level. Treatments were concentrations of liquid organic fertilizer of banana peels (0; 5; 10; 15; and 20%) and replicated three times. Data were analysed with analysis of variance and mean separation of Duncan’s New Multiple Range Test at 5%. Results demonstrated that 10% of liquid organic fertilizer of banana peels increased the growth of strawberry plants and shortened the time to flowering